Two minimally invasive fusion techniques for neurogenic claudication caused by degenerative lumbar spondylolisthesis: a minimum 2-year follow-up study - Cui, Wei; Wang, Yehui; Hou, Wei; Deng, Xuangeng (Frontiers in Neurology, 2025)
BackgroundNeurogenic claudication induced by degenerative lumbar spondylolisthesis (DLS) is a highly prevalent condition. In recent research, oblique lumbar interbody fusion with anterior fixation (OLIF-AF) has emerged as a favored minimally invasive approach for treating DLS. Nevertheless, there have been relatively few investigations that have compared this method with minimally invasive transforaminal lumbar interbody fusion (MIS-TLIF), which has long been considered the standard technique.AimTo compare the clinical and radiological outcomes of OLIF-AF and MIS-TLIF in patients suffering from single-level, low-grade degenerative lumbar spondylolisthesis that leads to neurogenic claudication.MethodsWe conducted a retrospective study of 57 patients who presented with neurogenic claudication secondary to single-level degenerative lumbar spondylolisthesis and underwent surgical treatment between May 2018 and December 2022. Of these 57 patients, 31 underwent oblique lumbar interbody fusion with anterior fixation (OLIF-AF) and 26 underwent minimally invasive transforaminal lumbar interbody fusion (MIS-TLIF). Every patient had a follow-up period of at least 2 years. The recorded and compared data included the perioperative indicators, follow-up outcomes, and imaging parameters between the two groups.ResultsPreoperatively, the two groups exhibited a comparable baseline in demographic data and clinical characteristics, including visual analog scale (VAS) scores, Oswestry Disability Index (ODI), disc height (DH), intervertebral space angle (ISA), spinal canal cross-sectional area (CSA) and slip percentage (SP). Postoperatively, both groups exhibited significant improvements in VAS and ODI scores. The OLIF-AF group demonstrated superior clinical outcomes in terms of operative time (125.7 ± 46.2 min vs. 202.1 ± 66.4 min, p < 0.001), estimated blood loss (58.6 ± 30.5 mL vs. 143.5 ± 46.8 mL, p < 0.001), and length of hospital stay (8.6 ± 2.5 days vs. 10.7 ± 3.5 days, p = 0.009) compared to the MIS-TLIF group. However, the incidence of perioperative complications did not differ significantly between the two groups (16.1% vs. 19.2%, p > 0.05). Radiographic assessment at the 2-year follow-up revealed significantly greater improvements in DH, ISA and CSA in the OLIF-AF group (p < 0.05). At the 2-year follow-up, there were no significant differences between the two groups in SP (9.6 ± 1.8 % vs. 9.4 ± 1.6 %), interbody fusion rate (93.5% vs. 92.3%), or cage subsidence rate (3.2% vs. 3.8%) (all p > 0.05). Although low back pain VAS, leg pain VAS, and ODI scores improved postoperatively in both groups compared with preoperative values, the OLIF-AF group showed greater improvement in low back pain VAS and ODI scores at 1 week and 3 months postoperatively.ConclusionBoth OLIF-AF and MIS-TLIF are efficient in treating neurogenic claudication resulting from degenerative lumbar spondylolisthesis (DLS). Nevertheless, OLIF-AF is associated with a shorter operation duration, reduced surgical trauma, and faster early recovery, while maintaining long-term effectiveness and safety comparable to those of MIS-TLIF.